PENGEMBANGAN PROTOTIPE E-HEALTH PASIEN TERINTEGRASI DENGAN ARDUINO UNO R3 - Muhaemin, Mumu; Ferga Prasetyo, Tri (Universitas Majalengka, 2019)
In this globalization era, the development of technology is developing so rapidly along with the advancing mindset of increasingly advanced human resources The development of information and communication technology is increasingly rapid, so that it encourages innovation and change that involves experimentation in various fields, including the health sector that applies the use of computers in its activities or commonly known as E-Health. E-Health or Electronic Health is the use of information and communication technology including electronics, telecommunications, computers and informatics to process various types of medical information, to carry out clinical services (diagnosis or therapy), administration and education. In E-health distance factor is not a problem because all of its activities are carried out through data connections and in realtime. The purpose of this study is to make the development of an integrated E-health prototype with Arduino R3. The benefit of this E-health prototype is that it can detect early symptoms of heartbeat abnormalities, help speed up the examination and initial diagnosis of the patient's health and speed up the examination of the patient.